Quick Shifter Prototype for Manual Motorcycle Gear Transition: Prototipe Quick Shifter untuk Pergantian Gigi Motor Manual - Alvi Qodrinas; Arief Wicaksono (Indonesian Journal of Innovation Studies, 2025)
General Background: Motorcycles are widely used transportation tools, and manual transmission systems require multiple steps during gear shifting, which can be difficult for novice riders. Specific Background: Conventional gear shifting involves reducing throttle, pulling the clutch, shifting gears, and reopening the throttle, which may lead to delays or engine stalling. Knowledge Gap: Existing manual systems still rely heavily on rider skill, with limited integration of automated electronic assistance for gear shifting. Aims: This study aims to design and develop a quick shifter prototype to simplify and accelerate gear shifting in manual motorcycles. Results: The prototype utilizes a push button switch as a trigger, an Arduino Nano as a controller, and a relay system to momentarily cut ignition for 0.1 seconds, allowing smooth gear transition. Testing results show that gear shifting was successfully performed across all gears from 1 to 6 within RPM ranges of 1,000–12,000. Novelty: The study presents a prototype-based integration of microcontroller and relay systems to support clutchless upshifting in manual motorcycles. Implications: The prototype demonstrates a practical approach to simplifying gear shifting operations and improving user convenience in motorcycle operation. Keywords: Motorcycle, Quick Shifter, Arduino Nano, Gear Shifting, Prototype System Key Findings Highlights Successful operation across full gear range under varying engine speeds Ignition cut mechanism enables seamless transition without clutch use Integrated hardware and software configuration supports system functionality